Detection of okadaic acid (OA) and tetrodotoxin (TTX) simultaneously in seafood samples using colloidal gold immunoassay. (July 2019) - Ling, Sumei; Li, Xiulan; Zhang, Danping; Wang, Ke; Zhao, Wenwen; Zhao, Qiang; Wang, Rongzhi; Yuan, Jun; Xin, Sijie; Wang, Shihua
Abstract: Tetrodotoxin (TTX) is a neurotoxin mainly responsible for severe neurological illness, and okadaic acid (OA) is another important lipophilic toxin to humans. In this study, we developed a gold strip for simultaneous detection of OA and TTX in real seafood samples. In the assay, the prepared nanoparticles (about 40 nm) was applied to conjugate with specific monoclonal antibodies against OA and TTX, and the resulted mixtures were used to capture its corresponding toxin in test strip. OA and TTX conjugates were coated as two test lines on the nitrocellulose membrane, and goat anti-mouse IgG was used to form the control line, forming three lines on the test strip. The visual detection limits (vLOD) of this immunoassay for OA and TTX were 0.75 and 15 ng/mL, respectively, and no cross reactions were observed in the process of detection. The visual assay for OA and TTX detection could be finished within 10 min. This study might provide a feasible method and good understanding for rapidly simultaneous detection for toxins based on immunoassay. Highlights: A colloidal gold test strip for simultaneous detection of OA and TTX was constructed. The detection limits for the OA and TTX were 0.75 ng/mL and 15 ng/mL, respectively. The visual assay for OA and TTX detection could be finished within 10 min.